Pengaruh Cognitive Behaviour Therapy (CBT) terhadap Pasien Gagal Ginjal Kronik di Unit Hemodialisa Rumah Sakit Husada Jakarta - Setyaningsih, Tri; Mustikasari, Mustikasari; Nuraini, Tuti (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
Chronic renal failure (GGK) or end-stage renal disease (PGTA), is one of the major diseases in the world. In addition to difficult to cure because it is irreversible can also cause psychososil disorders. This research was conducted on 27 respondents, using quasi experimental design pre-post test without control group. The results showed that there was a significant effect of CBT therapy on self-esteem level both cognitive and behavioral in patients with CRF (p value <0,000) and the opportunity to increase self-esteem in terms of behavior with CBT therapy was 43,9%. The conclusion of this study is that CBT therapy can improve the self-esteem of GGK patients undergoing hemodialysis therapy in he Husbandry Hemodialysis unit Jakarta.